Structural properties of chalcogenide glasses As₂Se₃ doped with manganese - Paiuk, O.P.; Revutska, L.O.; Stronski, A.V.; Gudymenko, A.Yo.; Stanchu, H.V.; Gubanova, A.A.; Kryskov, Ts.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The paper presents the results of studying structural properties inherent to chalcogenide glasses doped with manganese. Investigations of the structure were carried out using Raman spectroscopy and X-ray diffraction. The function of radial distribution of atomic density and Raman spectra have been obtained and analyzed.